NATIONAL PHYSICS OLYMPIADS FROM THE POINT OF VIEW OF PARTICIPANTS AND PHYSICS TEACHERS - Belogrudova, Ludmila; Dudareva, Inese; Kashcheyevs, Vyacheslavs; Voitkans, Arnis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The development of student's interests and skills is strategically important to foster their career choice in the field of science, technology and engineering, which is one of the goals of Latvia's National Development Plan for 2021-2027. Physics Olympiads can be used as one of the enrichment measures to supplement formal school teaching in raising student motivation and developing their skills and talents. We explore directions in which the existing system of Physics Olympiads can be improved, with the goals of reaching a wider audience of teachers and students and achieving further integration with the learning processes in schools. We have conducted a survey of physics teachers (NT=188), and participants (NP=486) of the second (county) stage of Latvian Physics Olympiad in January 2020. The aim of the survey was to find out: 1) What motivates students to participate and teachers to encourage participation in Physics Olympiads?  2) What resources are used for training? 3) What further support would students and teachers need for training for the Olympics? Based on the results of the survey, we propose specific measures to support teachers and students in their engagement with Physics Olympiads, report on the implementation progress, and give an outlook for the future.